2015
DOI: 10.11114/jets.v3i5.942
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Staff in Quality Improvement in Early Childhood

Abstract: There is international recognition of the importance of high quality services for young children with a consensus that three pillars contribute to quality improvement: adult: child ratios, staff qualifications and group size. In Australia over the past 5 years, early childhood policy has attempted to drive improvements in early childhood service quality through national regulations for both adult: child ratios and qualifications. However, a review of early childhood history demonstrates that service quality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Extant research indicates that leaders (Educational Leaders/Directors/Deputy Directors -the differentiation remains unclear in many circumstances) in the early years of implementing the National Quality Framework spent as much as a third of their time on compliance focused activities such as monitoring pedagogical documentation created by the educators they were supervising, and working on the compulsory accreditation standards (Garrock & Morrissey, 2013;Rouse & Spradbury, 2015;Sims et al, 2018a;Sims & Waniganayake, 2015). This research found that whilst many leaders thought they were doing relationship work with their staff, their perceptions of the way in which they performed their work did not reflect this approach.…”
Section: Within Australiamentioning
confidence: 99%
“…Extant research indicates that leaders (Educational Leaders/Directors/Deputy Directors -the differentiation remains unclear in many circumstances) in the early years of implementing the National Quality Framework spent as much as a third of their time on compliance focused activities such as monitoring pedagogical documentation created by the educators they were supervising, and working on the compulsory accreditation standards (Garrock & Morrissey, 2013;Rouse & Spradbury, 2015;Sims et al, 2018a;Sims & Waniganayake, 2015). This research found that whilst many leaders thought they were doing relationship work with their staff, their perceptions of the way in which they performed their work did not reflect this approach.…”
Section: Within Australiamentioning
confidence: 99%
“…ECEC leadership development has been linked to quality (Rodd, 2013), where effective leadership is expected as ‘the leader inspires changes in the quality of service delivery’ (Sims and Waniganayake, 2015: 190). Scholars have argued that good leadership should be inclusive and collaborative (Davis, 2012), distributed and collegial (Siraj-Blatchford and Manni, 2007), and more effective when transformational styles are employed (Lindon et al, 2016).…”
Section: Leadership Development and Childcare Markets In English Ececmentioning
confidence: 99%
“…In this line, several authors [26,27] state that it is essential to know the opinion of the professionals since it directly affects the design, dedication, and results of the service provided. Therefore, it is important to consider the perception of the professionals who compose the multidisciplinary teams in EI centres [1,28] for the design of specific measuring tools [29]. However, the perspective of professionals has been studied only as another dimension of service quality [28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to consider the perception of the professionals who compose the multidisciplinary teams in EI centres [1,28] for the design of specific measuring tools [29]. However, the perspective of professionals has been studied only as another dimension of service quality [28].…”
Section: Introductionmentioning
confidence: 99%